2012
DOI: 10.1159/000339129
|View full text |Cite
|
Sign up to set email alerts
|

Case of Unilateral Peripheral Cone Dysfunction

Abstract: Purpose: Peripheral cone dystrophy is a subgroup of cone dystrophy, and only 4 cases have been reported. We present a patient with unilateral peripheral cone dysfunction and report the functional changes determined by electrophysiological tests and ultrastructural changes determined by spectral domain optical coherence tomography (SD-OCT). Case: A 34-year-old woman complained of blurred vision in both eyes. Our examination showed that her visual acuity was 0.05 OD and 0.2 OS. A relative afferent pupillary defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Five cases of unilateral cone dystrophy have been reported [12][13][14][15], but the current case is not in the same category because of the residual foveal bulge. Previous studies have reported the electrophysiologic and clinicopathological findings in peripheral cone dystrophy [1][2][3][4][5][6][7]. The ff-ERG of peripheral cone 6 dystrophy shows attenuation or disappearance of the cone response similar to typical cone dystrophy [1,[4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five cases of unilateral cone dystrophy have been reported [12][13][14][15], but the current case is not in the same category because of the residual foveal bulge. Previous studies have reported the electrophysiologic and clinicopathological findings in peripheral cone dystrophy [1][2][3][4][5][6][7]. The ff-ERG of peripheral cone 6 dystrophy shows attenuation or disappearance of the cone response similar to typical cone dystrophy [1,[4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Kondo et al first determined the pathogenesis of peripheral cone dystrophy using electrophysiology [1]. Thereafter, some cases of peripheral cone dysfunction syndrome and peripheral cone dystrophy have been reported that were analyzed by electroretinography (ERG) and optical coherence tomography (OCT) [2][3][4][5][6][7]. However, in those reports the pathological analyses had been performed using spectral-domain OCT (SD-OCT).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the electrophysiologic and clinicopathological findings in peripheral cone dystrophy [1][2][3][4][5][6][7]. The ff-ERG of peripheral cone dystrophy shows attenuation or disappearance of the cone response similar to typical cone dystrophy [1,[4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the signs and symptoms of these patients were not manifested at an early stage in the more common type of PCD [ 4 ]. Mochizuki et al [ 5 ] presented a 34-year-old patient with unilateral peripheral cone dysfunction.…”
Section: Introductionmentioning
confidence: 99%